PENGARUH KINERJA KEUANGAN DAN HARGA SAHAM TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI PERIODE 2018-2021 - Joseph Fernando Darwin; Jimmy Tantra; Vito Royce; Namira Ufrida Rahmi; Putri Kemala Dewi (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The purpose of this study is to examine changes in financial data and market prices for producer shares on the IDX from 2018 to 2021, partially and simultaneously. Very extraordinary or volatile. In general, of course, it greatly influences the opinion of speculators or prospective economists from manufacturing issuers in Indonesia. The population is the total number of manufacturing companies on the IDX for the 2018–2021 period, or approximately 178 companies and a sample with a total of 112 units of analysis. Several linear regression analysis techniques are used in the research method. The results of the study are: Return on Investments, Earnings per Share, Dividend Yield and Share Prices have no partial or combined effect on Return of Shares of Industrial Companies Listed on the IDX for 2018-2021